Structural Features of Antiviral APOBEC3 Proteins are Linked to Their Functional Activities - Kitamura, Shingo; Ode, Hirotaka; Iwatani, Yasumasa (Frontiers in Microbiology, 2011)
APOBEC3 (A3) proteins are cellular cytidine deaminases that potently restrict the replication of retroviruses by hypermutating viral cDNA and/or inhibiting reverse transcription. There are seven members of this family including A3A, B, C, DE, F, G, and H, all encoded in a tandem array on human chromosome 22. A3F and A3G are the most potent inhibitors of HIV-1, but only in the absence of the virus-encoded protein, Vif. HIV-1 utilizes Vif to abrogate A3 functions in the producer cells. More specifically, Vif, serving as a substrate receptor, facilitates ubiquitination of A3 proteins by forming a Cullin5 (Cul5)-based E3 ubiquitin ligase complex, which targets A3 proteins for rapid proteasomal degradation. The specificity of A3 degradation is determined by the ability of Vif to bind to the target. Several lines of evidence have suggested that three distinct regions of A3 proteins are involved in the interaction with Vif. Here, we review the biological functions of A3 family members with special focus on A3G and base our analysis on the available structural information.